ANALISIS PENGARUH LITERASI KEUANGAN DAN PERSEPSI RISIKO TERHADAP BIAS EFEK DISPOSISI: IMPLIKASI DALAM PENGAMBILAN KEPUTUSAN FINANSIAL - Dwiyanto, Muhaswad; Saragih, Guntur Syahputra; Supriadi, Yudi Nur; Badawi, Moch Ridho (Gapenas Publisher, 2024)
This study aims to analyze the impact of financial literacy and risk perception on the disposition effect bias among students of the Faculty of XYZ. Using a quantitative approach, this research involves students from the Faculty of XYZ as the population, with a sample of 100 respondents selected through a probability sampling technique using simple random sampling. Data were collected through the distribution of questionnaires and analyzed using Partial Least Squares (PLS) method with the assistance of SmartPLS 3.0 software. The results show that financial literacy has a significant impact on the disposition effect bias, and risk perception also significantly affects the disposition effect bias. The novelty of this study lies in examining the influence of financial literacy and risk perception on the disposition effect bias among students, an area that has been limited in previous literature. The findings provide valuable insights into understanding the factors influencing financial decision-making among students and may serve as a basis for more effective financial literacy interventions among the younger generation